Measurement of the Length and Strength of Adhesive Interactions in a Nanoscale Silicon–Diamond Interface. Issue 9 (13th May 2015) - Jacobs, Tevis D. B.; Lefever, Joel A.; Carpick, Robert W.
<x xml:space="preserve">Abstract</x> The adhesive interactions between nanoscale silicon atomic force microscope (AFM) probes and a diamond substrate are characterized using in situ adhesion tests inside of a transmission electron microscope (TEM). In particular, measurements are presented both for the strength of the adhesion acting between the two materials (characterized by the intrinsic work of adhesion Wadh, int) and for the length scale of the interaction (described by the range of adhesion z0). These values are calculated using a novel analysis technique that requires measurement of the AFM probe geometry, the adhesive force, and the position where the snap‐in instability occurs. Values of Wadh = 0.66 J m−2 and z0 = 0.25 nm are extracted using this technique. This value of work of adhesion is 70% higher than the work of adhesion calculated if one uses a conventional paraboloidal asperity model. Comparing to literature, the work of adhesion obtained using the new method is significantly higher than most experimental and simulation values for similar material pairs. The discrepancy is attributed to nanoscale roughness, which was not accounted for previously. Furthermore, the value of the range of adhesion is comparable to previously reported values, but is significantly larger than the commonly assumed value of the interatomic spacing.